Cervical spondylitis - Nartono Kadri; Sularto Reksoprodjo (Paediatrica Indonesiana, 1973)
Tuberculous spondylitis in children is usually due to dissemination of tubercle bacilli by the blood stream from the initial infection which is inthe majority of cases a pulmonary primary tuberculosis.About five per cent of the large group of children pulmonary primarytubercolusis have (a) complication in bone and joint (Lincoln andSewell, 1963). Any bone of the body can be involved. The most common site, however, is the spine column of which the thoracic part, especiaUy the lower is the most common site. The cervical segments are next in order of frequency. Sularto et al. (1970), however, found that theupper part of the lumbar spine was the most common site of involvement.